Melito of Sardis on Tyranny and the Reign of Marcus Aurelius - Chrysovalantis Kyriacou (Religions, 2024)
The article examines perceptions of tyranny in Melito’s On Pascha and Apology, both written under Marcus Aurelius (161–180). This is the first systematic treatment of a key theme in Melito, approached not only from a theological perspective but also in the context of the Second Sophistic and Roman political developments. By proposing a more precise dating for On Pascha, we trace the development and consistency of Melito’s thought and arguments in regard to the relationship between Roman Empire and Christian communities in Asia Minor during the second half of the second century CE.